2019
DOI: 10.1016/j.jcm.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preterm Infant Massage by the Mother on the Mood of Mothers Having Preterm Infants

Abstract: Objective: The purpose of this study was to determine the effect of preterm infant massage by the mother on the mood state of mothers of preterm infants. Methods: This experimental study assessed 52 mothers of preterm infants (born at 30-37 weeks of gestation) hospitalized in the neonatal intensive care unit of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 32 publications
2
39
0
1
Order By: Relevance
“…The methods used to increase parental involvement during care include the Alberta Family Integrated Care (Alberta FiCare)(11), the Parent Participation Improvement Program (18), and involvement in nursing action or nursing implementation (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The methods used to increase parental involvement during care include the Alberta Family Integrated Care (Alberta FiCare)(11), the Parent Participation Improvement Program (18), and involvement in nursing action or nursing implementation (13).…”
Section: Discussionmentioning
confidence: 99%
“…This is because women are more susceptible than men to psychological problems such as depression, anxiety and other disorders (23). The birth of a premature baby can have a psychological impact on the mother, such as changes in mood, stress and depression (13). The treatment of premature infants requires parents to stay in the hospital, where the length of stay can be from days to months.…”
Section: Stress Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because women are more suspectible than men to psychological problems such as depression, anxiety and other disorders (23). The birth of a premature baby can have a psychological impact on the mother, such as changes in mood, stress and depression (13). Treatment of premature babies requires parent to stay in the hospital, where the length of stay can be from days to months.…”
Section: Stress Manajementmentioning
confidence: 99%
“…Increasing the participation of mothers in the care of premature babies can improve the mental health of mothers. Various methods were carried out by scientists, one of the studies conducted by Lotfalipour, et al, aimed to determine the effect of maternal involvement in one of the selected interventions, namely infant massage on the mother's mood (13). The intervention was carried out for five days, while the results of the study showed a greater improvement in mood compared to the control group (13).…”
Section: Stress Manajementmentioning
confidence: 99%